2023
DOI: 10.1039/d3ra04456d
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-like emerging 2D materials: recent progress, challenges and future outlook

Md. Mohi Uddin,
Mohammad Humaun Kabir,
Md. Ashraf Ali
et al.

Abstract: The exploration of the unique physiochemical properties of 2D materials, led by graphene in numerous aspects, the scientific community has been intrigued in excavating a new class of graphene-like 2D materials for next-generation technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 389 publications
0
3
0
Order By: Relevance
“…The range of values of n extends from 1 to 4 indicating the number of M-X-M layers in a particular MXene and value of x in T x can be less than or equal to 2. 34,36,[40][41][42][43][44][45] X can also represent oxygen as Michalowski et al studied the formation of oxycarbides aer the substitution of oxygen in carbide MXenes. 46 The composition space and synthesis of MAX and MXene are shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The range of values of n extends from 1 to 4 indicating the number of M-X-M layers in a particular MXene and value of x in T x can be less than or equal to 2. 34,36,[40][41][42][43][44][45] X can also represent oxygen as Michalowski et al studied the formation of oxycarbides aer the substitution of oxygen in carbide MXenes. 46 The composition space and synthesis of MAX and MXene are shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Two dimensional (2D) materials have drawn significant attentions among the materials scientists because of their wide range of technological and biomedical applications [1][2][3][4][5][6][7][8][9][10][11][12]. The advantages of 2D over three dimensional (3D) materials are mainly attributed to the increase in exposed surface area to volume ratio, which in turn alter their electronic band structures and hence their associated mechanical, electrical, thermal and optical properties [4,[13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of the battery industry, potassium-ion batteries (PIBs) are increasingly sought aer. [1][2][3][4] In this regard, inexpensive and sustainable organic redox active compounds are becoming highly promising electrode materials for PIBs. [5][6][7] Different research groups have demonstrated that organic electrodes possess signicant advantages, such as high capacity (naphthalene-1,4,5,8-tetracarboxylic acid dianhydride, NTCDA; 8,9 croconic acid; 10 and 2,6-diamino anthraquinone, DAQ 11 ), low cost, 12 rich raw materials, 13 and strong designability of structure.…”
Section: Introductionmentioning
confidence: 99%